A combination of four planning models for use in First Nations environmental health - Lüsgen, Birgit (Author); Booth, Annie; University of Northern British Columbia (Degree granting institution) (University of Northern British Columbia, 2006)
This project is an inquiry into understanding community-based planning models that may be used for First Nations' environmental health to contribute to more equitable partnerships. The purpose of this project was to conduct a review of the literature in order to select planning models that could better address the environmental health needs in relation to assessment, ecological considerations, culturally sustainable community development, and comprehensive First Nations community planning. My questions in this inquiry were: "Which community-based planning approaches may be used for First Nations environmental health programs and projects?" and "What specific models when combined together might be used by First Nations people, environmental health professionals; and others in the planning of environmental health programs and endeavours that contribute to the development of healthy, sustainable First Nations communities?" To answer these questions, and following an extensive review of the literature, I focused on two books, one article, and one manual as contributions to the field of environmental health planning and the importance of using models respectful of culture. The outcomes of the inquiry were enhanced by my own professional experience within First Nations environmental health and an awareness of planning between cultural paradigms. As a result, this project demonstrates that a select variety of planning models need to be considered as a foundation for developing healthy sustainable communities in order to connect environmental health with long-range comprehensive community planning. Such an opportunity offers First Nations and non-First Nations planners a way to proceed that has the potential to address the present, complex needs and future aspirations of community members within a larger regional, global context. The original print copy of this thesis may be available here: http://wizard.unbc.ca/record=b1309827